PREDICTORS OF SUCCESSFUL URINARY STONE TREATMENT BY EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY (Iraqi Journal of Medical Sciences, 2016)
Background:In spite of the recent advances in the endoscopic treatment of urinary stones, extracorporeal shock wave lithotripsy (ESWL) is still the treatment of choice for most renal and upper ureteric stones; however the outcome depends on multiple factors.Objective:To investigate the effects of stone density, as measured by Hounsfield Units (HU) by non-contrasted computerized tomography (CT), stone size and stone location on ESWL treatment outcome of urinary calculi.Methods: A prospective study that included 65 patients. Data collection and patient evaluation were performed in Al-Salam Teaching Hospital in Mosul, in the period from March 2012 to December 2012. Patients were submitted to clinical, biochemical and radiological assessments followed by ESWL treatment. Statistical analyses using chi-square, analysis of variance (ANOVA), correlation, regression were performed for statistical significance between ESWL treatment, stone fragmentation and stone density, size and location in the renal pelvicalyseal system.Results: ESWL success rate was high (92%) for low density stones (< 500 HU). ESWL treatment outcome and stone size were inversely related. CT stone densities of 700 HU or less were almost always successfully treated by ESWL. CT stone density and stone size combined account for nearly 74% of the variation in the number of shock waves required to attain fragmentation. Stones located in lower calyceal area had less success rates.Conclusion:Stone density measurement is helpful to predict the success of ESWL for urinary stones, stones with higher density, large size and lower location may better be managed by percutaneous nephrolithotomy or endoscopic procedures.Key words:CT stone density, ESWL, none contrasted CT scan (NCCT).
Keywords: CT stone density; ESWL; none contrasted CT scan NCCT